2015
DOI: 10.4103/1008-682x.153847
|View full text |Cite
|
Sign up to set email alerts
|

Negative biomarker based male fertility evaluation: Sperm phenotypes associated with molecular-level anomalies

Abstract: Biomarker-based sperm analysis elevates the treatment of human infertility and ameliorates reproductive performance in livestock. The negative biomarker-based approach focuses on proteins and ligands unique to defective spermatozoa, regardless of their morphological phenotype, lending itself to analysis by flow cytometry (FC). A prime example is the spermatid specific thioredoxin SPTRX3/TXNDC8, retained in the nuclear vacuoles and superfluous cytoplasm of defective human spermatozoa. Infertile couples with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 80 publications
0
60
0
5
Order By: Relevance
“…Muratori et al (2005) and Varum et al (2007) reported the opposite results. These discrepancies could be explained either by hypo-functionality of ubiquitin-based spermatozoa selection and degradation in epididymis (Eskandari-Shahraki et al 2013) or by detection of ubiquitinated proteins, albeit not those on the sperm surface, that are intrinsic to normal spermatozoa (Sutovsky et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Muratori et al (2005) and Varum et al (2007) reported the opposite results. These discrepancies could be explained either by hypo-functionality of ubiquitin-based spermatozoa selection and degradation in epididymis (Eskandari-Shahraki et al 2013) or by detection of ubiquitinated proteins, albeit not those on the sperm surface, that are intrinsic to normal spermatozoa (Sutovsky et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These factors permit the spermatozoon to penetrate extracellular matrix barriers containing hyaluronic acid (Modelski et al., ). Other proteins detected using flow cytometry that are potential sperm biomarkers include a truncated form of KIT tyrosine kinase (Muciaccia et al., ), the spermatic specific thioredoxin‐3 protein (SPTRX‐3) (Buckman et al., ) other thioredoxins, peroxiredoxins, ubiquitin and ubiquitin‐like modifier proteins (Sutovsky, Aarabi, Miranda‐Vizuete, & Oko, ). Nuclear proteins have also been investigated using flow cytometry (Zhong et al., ).…”
Section: Single‐cell Analysis In Sperm Proteomics: Flow Cytometrymentioning
confidence: 99%
“…Following this fusion, sperm factor(s) is released into the ooplasm to hydrolyse phosphatidylinositol 4, 5‐biphosphate (PIP 2 ) into the diacylglycerol (DAG) and inositol triphosphate (IP 3 ). Then, IP 3 binds to its receptors located in the calcium intracellular store membrane to release calcium from ooplasmatic store to initiate oocyte activation which consequently leads to resumption of meiosis, progressive of metaphase to anaphase and early embryonic development (Sutovsky, Aarabi, Miranda‐Vizuete, & Oko, ; Swann & Lai, ; Yeste, Jones, Amdani, Patel, & Coward, ). So far, several sperm factors involved in oocyte activation are suggested.…”
Section: Introductionmentioning
confidence: 99%